Thermal behavior and dehydroxylation kinetics of naturally occurring sepiolite and bentonite - Yilmaz, Muge Sari; Kalpakli, Yasemen; Piskin, Sabriye (SPRINGER, 2013)
Sepiolite and bentonite have a wide range of industrial applications based on their physicochemical properties such as surface area, thermal behavior, chemical composition, and mineralogic composition. The thermal behavior and kinetics of naturally occurring sepiolite and bentonite were determined in order to give an idea about the potential use of naturally occurring clay minerals in possible applications. Naturally occurring sepiolite and bentonite samples were heated to the temperature that was achieved at the end of the dehydroxylation process. Mineralogic and thermal characteristics of raw and heat treated samples were investigated by X-ray diffraction, Fourier transform infrared spectroscopy, and nitrogen adsorption/desorption analyses. Changes in the structure following heat treatment were used for the evaluation of the dehydroxylation properties of the samples. The dehydroxylation properties of the minerals are strongly affected by the crystal structure. Kinetic analyses, which were related to the dehydroxylation of naturally occurring sepiolite and bentonite, were conducted using dynamic thermogravimetry/derivative thermogravimetry analysis under nitrogen atmosphere. Flynn-Wall-Ozawa, Kissenger-Akahira-Sunose, and Friedman isoconversional methods were used to determine the activation energies of the dehydroxylation reactions of the samples. The results indicate that the activation energy of naturally occurring sepiolite showed a little variation at a particular conversion rate (0.3-0.7), while the activation energy of naturally occurring bentonite showed a significant variation within the range of variation of the conversion rate. The present study shows that the dehydroxylation reactions of naturally occurring sepiolite and bentonite were single mechanism reaction and complex mechanism reaction, respectively.
Keywords: Naturally occurring sepiolite; Bentonite; Thermal treatment; Dehydroxylation; Kinetics; Thermal behavior; THERMOGRAVIMETRY; HEAT; Thermodynamics; Chemistry